2014
DOI: 10.1021/bc500445d
|View full text |Cite
|
Sign up to set email alerts
|

Methyleneation of Peptides by N,N,N,N-Tetramethylethylenediamine (TEMED) under Conditions Used for Free Radical Polymerization: A Mechanistic Study

Abstract: Free radical polymerization is often used to prepare protein and peptide-loaded hydrogels for the design of controlled release systems and molecular imprinting materials. Peroxodisulfates (ammonium peroxodisulfates (APS) or potassium peroxodisulfates (KPS)) with N,N,N,N-tetramethylethylenediamine (TEMED) are frequently used as initiator and catalyst. However, exposure to these free radical polymerization reagents may lead to modification of the protein and peptide. In this work, we show the modification of lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…It was assumed that the grafting of PNIPAAm chains onto Cs occurred at the carbon C-2 position of the pyranose ring. The formation of amine radicals is highly favored over hydroxyl radicals [54,55], supporting work by Shirangi et al [56] that demonstrated that primary amines exhibit increased affinities for the α-TEMED radical species (Figure 9a). The aforementioned evidence points to the directed radical formation C-2-NH 2 species of chitosan [57].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It was assumed that the grafting of PNIPAAm chains onto Cs occurred at the carbon C-2 position of the pyranose ring. The formation of amine radicals is highly favored over hydroxyl radicals [54,55], supporting work by Shirangi et al [56] that demonstrated that primary amines exhibit increased affinities for the α-TEMED radical species (Figure 9a). The aforementioned evidence points to the directed radical formation C-2-NH 2 species of chitosan [57].…”
Section: Discussionsupporting
confidence: 79%
“…Hydrogen atom abstraction could have occurred from NIPAAm homopolymer but was more likely from the radical initiators [58]. In addition, the higher concentrations of TEMED (0.2 mmol) compared to APS (0.131 mmol) supported the likelihood of increased formation of TEMED radical to facilitate the secondary initiation mechanism (Figure 9b) [56]. In contrast to gel permeation chromatography (GPC) and high-performance liquid chromatography (HPLC), for which retention times do not provide specific detail on the structure of the graft [59], or preparative liquid chromatography-mass spectrometry (LC-MS) methods where mass spectrometry (MS) fragmentation spectra would be the same irrespective of where the NIPAAm chain extension is grafted onto the Cs, the grafting position could be confirmed with the use of 1 H-NMR in dimethyl sulfoxide (d6-DMSO).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the effect of the nucleophile scavenger NMM on free radical-induced TRPA1(A) activation was tested in heterologous frog oocytes. Addition of tetramethylethylenediamine (TEMED) and ammonium persulfate (APS) initiates polymerization reactions, such as solidification of polyacrylamide gel, by generating free radicals ( Shirangi et al, 2015 ). To examine the responsiveness of TRPA1(A) to free radicals, frog oocytes expressing agTRPA1(A) were exposed to a mixture of 0.01 mM TEMED and 0.1 mM APS.…”
Section: Resultsmentioning
confidence: 99%
“…This can be solved by increasing the crosslink density of nanogels to stably entrap their payloads during gel formation. However, once the biotherapeutics are loaded in hydrogel particles during preparation, this might result in chemical modification of the loaded molecules [40][41][42][43]. In other alternative methods, strongly charged biotherapeutics, such as nucleic acids, can be post-loaded into oppositely charged nanogels and stably immobilized by strong electrostatic interaction under physiological conditions [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%